Legal Principles of Agreements in Fixed-Term Employment Agreements (Study of PT Abc's Partnership Pattern Employment Agreements After Management Decision) - Kusumadewi, Dimitria Pawestri; Joesoef, Iwan Erar; Wati, Diani Sadia (Journal of Law, Politic and Humanities, 2025)
Employment relations in Indonesia are regulated in the 1945 Constitution and the Manpower Law, which guarantee workers' rights to employment and fair treatment. However, in practice, there has been a shift in terminology and work patterns, especially with the implementation of partnership patterns by companies to avoid employment obligations. This study highlights the implementation of partnership patterns at PT ABC which changes the status of warehouse workers to partners, thereby eliminating normative rights such as minimum wages, social security, and other benefits. Changes in terminology such as "wages" to "service fees" and "working hours" to "service hours" blur the boundaries between employment and partnership relationships. This leads to labor exploitation. This study analyzes the principles of employment agreements in partnership patterns and their impact on the protection of warehouse workers at PT ABC. The results of the study indicate that partnership patterns can be a legal loophole for companies to avoid employment obligations, so stricter regulations are needed to protect workers' rights.